The impact of morphophonological patterns on verb production: evidence from acquired morphological impairment. (1st February 2019) - Rimikis, Stacey; Buchwald, Adam
ABSTRACT: Although much of the research on morphology and aphasia has focused specifically on the distinction between regular and irregular verb production, individuals with aphasia often present with differences in performance within these categories. While these within-category differences are relatively understudied, they have the potential to inform our understanding of the morphological processing system and treatment protocols for morphological impairment. The present study examines how morphophonological patterns in English impact past-tense production within the categories of regular and irregular verbs based on errors of an individual with acquired morphological impairment. Acquired morphological impairment was demonstrated by performance on two reading tasks. First, the individual produced more final consonant deletion errors in morphologically complex words ( prays →[pre]) compared to homophones ( praise →[pre]). Second, morphological deletion errors were found to occur at comparable rates for inflected regular verbs ( sinned→sin ) and inflected irregular verbs ( won→win ), whereas the analogous error (e.g. ton→tin ) never occurred on the monomorphemic pairs. In order to examine differences within each category, we used a past-tense elicitation task designed to analyse the effect of differences in morphophonological pattern frequency on accuracy and error patterns in production. We found production of both regular and irregular verbs was affected by the extent to which different morphophonological patterns are supported in the language (i.e. the number of phonologically similar words within the lexicon which take the same inflectional change). These results provide evidence that morphophonological patterns are encoded in a way that impact morphological production, a finding which has both clinical and theoretical implications.